Narasi Budaya dalam Pembentukan Citra Kota Tua sebagai Destinasi Heritage Urban - Mezi Julian; Lilik Edi Saputro; Syaharuddin Syaharuddin (Jurnal Ilmiah Dan Karya Mahasiswa, 2026)
Jakarta Old Town is one of Indonesia’s prominent urban heritage areas with significant potential for developing a destination image based on cultural narratives. However, its utilization has not yet been fully integrated. This study aims to analyze how cultural narratives are constructed and disseminated, as well as their influence on tourists’ perceptions in shaping the image of Jakarta Old Town as an urban heritage destination. The research employed a qualitative approach through field observations, in-depth interviews, and documentation, with data analyzed using the Miles and Huberman interactive model. The findings reveal that the prevailing narratives are still predominantly focused on visual attractions and colonial history, while the social dimensions and local cultural life remain underrepresented. As a result, tourists tend to perceive Jakarta Old Town more as a recreational and photography destination rather than as a space for cultural education. These findings indicate a gap between the objectives of sustainable urban heritage destination development and the realities of on-site practices. Therefore, a more integrated and participatory cultural narrative strategy is needed to strengthen the destination’s heritage identity and enhance its image.